Non‐structural protein 1‐specific antibodies directed against Zika virus in humans mediate antibody‐dependent cellular cytotoxicity. Issue 2 (14th June 2021) - Sanchez Vargas, Luis A.; Adam, Awadalkareem; Masterson, Mary; Smith, Madison; Lyski, Zoe L.; Dowd, Kimberly A.; Pierson, Theodore C.; Messer, William B.; Currier, Jeffrey R.; Mathew, Anuja
Abstract: There is growing interest in understanding antibody (Ab) function beyond neutralization. The non‐structural protein 1 (NS1) of Zika virus (ZIKV) is an attractive candidate for an effective vaccine as Abs against NS1, unlike the envelope or premembrane, do not carry the risk of mediating antibody‐dependent enhancement. Our aim was to evaluate whether ZIKV NS1 Abs elicited following natural infection in humans can mediate antibody‐dependent cellular cytotoxicity (ADCC). We evaluated the isotype specificity of ZIKV‐specific Abs in immune sera and supernatants from stimulated immune PBMC and found that Abs against ZIKV NS1 and virus‐like particles were predominantly of the IgG1 isotype. Using a recently developed FluoroSpot assay, we found robust frequencies of NS1‐specific Ab‐secreting cells in PBMC of individuals who were naturally infected with ZIKV. We developed assays to measure both natural killer cell activation by flow cytometry and target cell lysis of ZIKV NS1‐expressing cells using an image cytometry assay in the presence of ZIKV NS1 Abs. Our data indicate efficient opsonization of ZIKV NS1‐expressing CEM‐NK R cell lines using ZIKV‐immune but not ZIKV‐naïve sera, a prerequisite of ADCC. Furthermore, sera from immune donors were able to induce both NK cell degranulation and lysis of ZIKV NS1 CEM‐NK R cells in vitro. Our data suggest that ADCC is a possible mechanism for ZIKV NS1 Abs to eliminate virally infected target cells. Abstract : ZIKV‐immune sera efficiently opsonize CEM‐NKR cell lines expressing ZIKV NS1. Sera from immune donors can induce both NK cell degranulation and lysis of ZIKV NS1 CEM‐NKR cells in vitro.